Gender Differences in Clothing Worn in Current Popular Comic Books - Jossy, Kyle Landon (MacEwan University Student eJournal, 2015)
This study looked at how males and females were portrayed, based on the amount of skin shown in the clothing worn. A Content analysis was performed on a sample of 20 randomly selected popular comics from the last 3 years. Both male and female characters were rated on how much skin they showed in three clothing categories; neck line, sleeve length, and lower body. Results showed that in all 3 categories, women consistently wore more revealing clothing. The findings demonstraetd that the comic book industry is comparable to other forms of media, in the sexualization of female characters, by having them wear more revealing clothing.